Durable hybrid electrocatalysts for proton exchange membrane fuel cells. (November 2020) - Xiao, Fei; Xu, Gui-Liang; Sun, Cheng-Jun; Hwang, Inhui; Xu, Mingjie; Wu, Hsi-wen; Wei, Zidong; Pan, Xiaoqing; Amine, Khalil; Shao, Minhua
Abstract: The low durability of carbon-based non-precious metal electrocatalysts hinders their practical applications in proton exchange membrane fuel cells (PEMFCs). In this study, we rationally design a hybrid Pt-Fe-N-C electrocatalyst with unprecedented durability. It consists of abundant Pt and Fe single atoms homogeneously dispersed on the nitrogen-doped carbon support and a small amount of Pt-Fe alloy nanoparticles. A PEMFC with Pt-Fe-N-C as the cathode shows a larger peak power density (0.75 W cm −2 ) than that with Fe-N-C as the cathode (0.50 W cm −2 ). The remarkable durability of Pt-Fe-N-C is reflected from no noticeable drop in the half-wave potential after 70000 potential cycles between 0.6 and 1.0 V in the liquid cell, and 80% current retention after 85 h of potential hold at 0.4 V in the fuel cell. This work demonstrates the feasibility of improving the durability of Fe-N-C material via ultra-low Pt doping and makes non-precious metal electrocatalysts be close to achieving commercial metrics. Graphical abstract: A hybrid Pt-Fe-N-C electrocatalyst consisting of abundant Pt and Fe single atoms homogeneously dispersed on the nitrogen-doped carbon support shows excellent activity toward oxygen reduction reaction and unprecedented durability. The current only drops 20% after 85 h of potential hold at 0.4 V in a proton exchange membrane fuel cell test, which is much better than regular Fe-N-C. Image 1 Highlights: Pt-Fe-N-C electrocatalyst consists of atomically dispersed Pt and Fe atoms and Pt-Fe alloy nanoparticles. Pt-Fe-N-C shows no noticeable activity decay after 70000 potential cycles between 0.6 and 1.0 V in RDE. Pt-Fe-N-C shows only 20% current drop at 0.4 V for 85 h in fuel cell testing.